Enhanced derivation of human pluripotent stem cell-derived cortical glutamatergic neurons by a small molecule - Shi-Ying Cao (Nature Portfolio, 2017)
Abstract Human pluripotent stem cells (hPSCs) play important role in studying the function of human glutamatergic neurons and related disease pathogenesis. However, the current hPSC-derived cortical system produced a significant number of inhibitory GABAergic neurons that reduced the purity of excitatory neurons. In this study, we established a robust hPSC-derived cortical neurogenesis system by applying the SHH inhibitor cyclopamine. Cyclopamine specified the dorsal cortical fate in a dose-dependent manner and enhanced the generation of cortical glutamatergic neurons, expressing PAX6, TBR1, TBR2, CTIP2, SATB2, and vesicular glutamate transporters (vGLUT). In contrast, the ventral patterning was inhibited and the GABAergic neurons were significantly reduced to 12% with the treatment of cyclopamine. In addition, we applied our current method to generate trisomy 21 iPSC-derived glutamatergic neurons that showed a robust reduction of vesicular glutamate transporters in the glutamatergic neurons with trisomy 21, revealing the developmental deficits in cortical glutamatergic neurons. Our method enriched the generation of cortical glutamatergic neurons which may facilitate the study of human neurological diseases and cell therapy.